The Implementation of Flipped Classroom and Course Review Horay to Increase Learning Activity and Outcomes - Agustiningrum, Arfiyanti (Unversitas Negeri Malang, 2018)
The observations result from Social Eleventh Graders at 2 MAN Batu, showed that the learning activity andÂ learning outcomes of Economics are still under standard amounted to 74. This was due to delivery of materials still use one direction methode. Students do not have the readiness for learning activities in the classroom. These things have an impact on low activity and student learning outcomes. This research aims to increase the activity and student learning outcomes in Social Eleventh Graders at 2 MAN Batu by implementing Flipped Classroom and Course Review Horray (CRH) learning model based lesson study. This research consisted of two cycles. The learning outcomes measured by the value of group working and the tests carried out at each end of the cycle.The results of student learning activities in the first cycle was 58 and the second cycle the stucdent learning activities value increased to 72. The research result of students learning outcomes in the first cycle was 75% and the second cycle increased to 89,29%.Â Based on the result of the classroom, the first conclusion of application of Flipped Classroom and Course Review Horray (CRH) learning models can be applied in the learning process on Economic subjects. Second, the application of Flipped Classroom and Course Review Horray (CRH) learning models to increase the students' learning activities on Economic subjects. The third application of Flipped Classroom and Course Review Horray (CRH) learning models can improve student learning outcomes on economic subjects.